Adsorption of Oleate Anions on to Cationized Lignocelluloses - H. Zghida; M.H.V. Baouab; R. Gauthier (Adsorption Science & Technology)
Oleic acid and its salts are present among the toxic pollutants in olive oil mill wastewaters. Four lignocellulosic materials modified by grafting quaternary ammonium groups have been tested for the adsorption of the oleate anion from aqueous solutions, viz. cotton fibres, viscose fabric, wood sawdust and maize cob powder. As a result of their strong ionic interactions, the carboxylate moities were entrapped at a rate equivalent to the ammonium content of the support. Furthermore, when this charged support was left in contact with the polluted solution without agitation, an additional quantity of pollutant was adsorbed due to associations by the hydrophobic tails of the oleate moities. Partial desorption was achieved in 1 M HCl solution.